Monitoring System Of Radon Gas Concentration In Groundwater In Real-Time For Earthquake Detection - Tio Andrian; Makhsun Makhsun (Sustainable Environmental and Optimizing Industry Journal, 2022)
Several studies that have been carried out can identify signs of an impending earthquake. One example of changes in the concentration of Rn (Radon) in the area affected by an earthquake. The purpose of this study is to design and create a prototype of an earthquake early detection system through real-time measurement of radon gas concentrations in the air where the measurement data results can be uploaded to the internet network and viewed by users in real time through a site. To detect it, a scintillation detector is used, in the design of the detector system the ZnS(Ag) scintillation type will be used. Data analysis was carried out in several ways, stability analysis of the count by measuring n times at the same concentration of radon gas and counting time, counting efficiency, calibration of counting and detection of limits. The data monitoring system is carried out through the website in real-time. Data is sent using an internet provider with sim900 every minute to 58 every hour. From the tests carried out on tap water continuously in the BATAN market area for 24 hours, it can be seen on the site that the average concentration value of Radon compounds in tap water at that location is 59.91 Bq/M3 where the total concentration is still below the threshold value. set by the ICRP (International Commission on Radiological Protection) is around 200 Bq/M3.